2018
DOI: 10.5114/pm.2018.74896
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the teach-back method in improving self-care activities in postmenopausal women

Abstract: IntroductionMenopause is a physiological process during which women can improve their quality of life by taking proper self-care measures. Performing self-care requires proper and effective training. The present study was conducted to investigate the effect of self-care training programs based on the teach-back method on the self-care status in postmenopausal women.Material and methodsThe present clinical trial was conducted in 2016 in Gonabad, in the east of Iran. Eighty postmenopausal women, whose last menst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“… 24 , 27 , 28 However, clinical evidence shows that people recall and retain information better with the teach-back method; thus we adopted this approach. 40 , 41 , 42 , 43 , 44 …”
Section: Methodsmentioning
confidence: 99%
“… 24 , 27 , 28 However, clinical evidence shows that people recall and retain information better with the teach-back method; thus we adopted this approach. 40 , 41 , 42 , 43 , 44 …”
Section: Methodsmentioning
confidence: 99%
“…This teach-back enhanced education ranged from brief sessions to more complex training. Nine studies [38,41,43,46,48,49,51,53,54] comprised more than one education session over the study period (range 2-11); brochures or written information were given in five studies [39,42,47,53,57] to aid the teach-back process; and demonstration of a technique was used in two studies [47,55]. There were four studies in which teach-back was delivered as a less structured approach; two of these focused on training clinicians to use teach-back as part of their routine care [31,40], and two studies [44,56] trained nursing staff to use teach-back when providing discharge instructions in the ED (Table 2).…”
Section: Delivery Of Teach-backmentioning
confidence: 99%
“…Of the 20 included studies, only 10 [39, 40, 44, 48, 51-54, 56, 57] reported sufficient information regarding implementation of teach-back. Of the remaining 10 studies, three [42,45,50] did not report any details related to implementation and seven [38,41,43,46,47,49,55] delivered teach-back via research staff, meaning that implementation strategies were not relevant in clinical practice, but for research purposes only (Table 2).…”
Section: Implementation Strategiesmentioning
confidence: 99%
“…It is in fact a strategy to cope with life events and stressors. Advances in medical technology and increases in healthcare costs, importance of health maintenance by individuals and communities based on human needs, increasing personal responsibility towards personal health, and reduced availability of healthcare services due to population growth have turned SC into an important determinant of health and quality of life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%